Almost starring Skinnybones - Park, Barbara (Alfred A. Knopf, 1988)
Irrepressible, twelve-year-old Alex is convinced that he will be a star and impress his schoolmates when, as the winner of a cat food essay contest, he is asked to make a commercial for national television.